The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1590/s1413-85571999000200006
|View full text |Cite
|
Sign up to set email alerts
|

Testes e provas psicológicas em Portugal

Abstract: SIMÕES, M. R; GONÇALVES, M. M. e ALMEIDA, L. S (Eds.) (1999). Testes e Provas Psicológicas em Portugal (vol. II). Braga: APPORT/SHO.A prática da Avaliação Psicológica que constitui, reconhecidamente, uma tarefa básica profissional da Psicologia, tem sido discutida e estudada em vários países.A presente obra tem como editores os pesquisadores Leandro S. Almeida, Mário R. Simões e Miguel M. Gonçalves e consiste no segundo volume da publicação anterior "Provas Psicológicas em Portugal". O livro em questão, reúne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
0
0
0
1
Order By: Relevance
“…Ferreira and Castela [37] found that a higher frequency of suicidal ideation is associated with a higher score on the assessment. The assessment demonstrated strong internal consistency, with a Cronbach's alpha value of 0.96 [37]. Item-total correlation values ranged from 0.21 to 0.86, but most were between 0.70 and 0.80 [37].…”
Section: Instrumentsmentioning
confidence: 95%
See 3 more Smart Citations
“…Ferreira and Castela [37] found that a higher frequency of suicidal ideation is associated with a higher score on the assessment. The assessment demonstrated strong internal consistency, with a Cronbach's alpha value of 0.96 [37]. Item-total correlation values ranged from 0.21 to 0.86, but most were between 0.70 and 0.80 [37].…”
Section: Instrumentsmentioning
confidence: 95%
“…Suicidal Ideation Questionnaire (SIQ): The Suicidal Ideation Questionnaire (SIQ) was used to assess the severity of suicidal ideation in adolescents and adults. Initially developed by Reynolds [36], the questionnaire was translated and adapted for the Portuguese population by Ferreira and Castela [37]. The SIQ is a self-report instrument consisting of 30 items, answered on a Likert-type scale with seven response alternatives, ranging from 0 (never had this thought) to 6 (almost every day).…”
Section: Instrumentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Como instrumento de coleta de dados utilizou-se o Questionário de Ideação Suicida (Suicidal Ideation Questionnaire -SIQ), na versão portuguesa, traduzida e validada (Reis, 1999). O SIQ tem por objetivo avaliar a gravidade dos pensamentos e cognições suicidas em adolescentes e adultos jovens, através de 30 itens, com uma escala de resposta tipo likert que varia de 0 (nunca tive este pensamento) a 6 (quase todos os dias penso nisso), podendo o resultado variar entre 0 e 180.…”
Section: Metodologiaunclassified